2022
DOI: 10.1177/09636897221122997
|View full text |Cite
|
Sign up to set email alerts
|

METTL3-Mediated m6A Modification of lncRNA MALAT1 Facilitates Prostate Cancer Growth by Activation of PI3K/AKT Signaling

Abstract: Accumulating data show that N6-methyladenosine (m6A) methyltransferase METTL3 and long noncoding RNA MALAT1 act pivotal roles in multiple malignancies including prostate cancer (PCa). However, the role and molecular mechanism underlying METTL3-mediated m6A modification of MALAT1 in PCa remain undocumented. The association of METTL3 and MALAT1 expression with clinicopathological characteristics and prognosis in patients with PCa was analyzed by quantitative real-time polymerase chain reaction (qRT-PCR), Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The high expression of METTL3 has been discovered in PCa previously. 39 RT-qPCR and Western blotting found that METTL3 expression in PCa cell lines (LNCaP, DU145, LAPC-4, VCaP) was observably elevated relative to prostate epithelial cells RWPE-1 (all p < .05) (Figure 1A,B), which was the highest in DU145 cells. Therefore, cell line DU145 was selected for subsequent studies.…”
Section: Interference With Mettl3 Suppressed Pca Cell Growthmentioning
confidence: 97%
“…The high expression of METTL3 has been discovered in PCa previously. 39 RT-qPCR and Western blotting found that METTL3 expression in PCa cell lines (LNCaP, DU145, LAPC-4, VCaP) was observably elevated relative to prostate epithelial cells RWPE-1 (all p < .05) (Figure 1A,B), which was the highest in DU145 cells. Therefore, cell line DU145 was selected for subsequent studies.…”
Section: Interference With Mettl3 Suppressed Pca Cell Growthmentioning
confidence: 97%
“…As a lncRNA, the metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is oncogenic in numerous tumours progressions ( Fan et al, 2014 ; Jen et al, 2017 ). Yuan et al ( Mao et al, 2022 ) confirmed that METTL3 could upregulate the m 6 A level of LncRNA-MALAT1, which activates the PI3K/AKT signaling pathway and promotes the growth and invasion of PCa. The molecular mechanisms of m 6 A methylation modifications in tumour cells have recently been studied.…”
Section: Role Of M 6 a Regulators In The Progressi...mentioning
confidence: 99%
“…Studies of writers on PCa have primarily focused on the regulatory component METTL3. Recent studies have indicated that METTL3 plays an oncogenic role in PCa ( Cai et al, 2019 ; Li et al, 2020a ; Li et al, 2020b ; Ma et al, 2020 ; Yuan et al, 2020 ; Chen et al, 2021a ; Ma et al, 2021 ; Liu et al, 2022a ; Wang et al, 2022a ; Mao et al, 2022 ; Chen et al, 2023 ). Only one study has suggested that it is a carcinogenic tumour suppressor ( Jia et al, 2022 ).…”
Section: Role Of M 6 a Regulators In The Progressi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have linked the lncRNA MALAT1 and the m 6 A methyltransferase METTL3 to malignancy progression in PCa. The m 6 A modification of lncRNA MALAT1 can be mediated by METTL3, thereby activating the PI3K/AKT signaling pathway, which promotes malignancy progression in PCa ( 90 ). Elevated levels of the lncRNA nuclear enriched abundant transcript (NEAT)1-1 recognize and activate the activity of CYCLOINL1 and form a different complex with extreme levels of CDK19 in PCa, which ultimately acts on the promoter Runt-related transcription factor 2 (RUNX2).…”
Section: A and Lncrnas In Cancer Metabolismmentioning
confidence: 99%